2002
DOI: 10.1111/j.1540-9740.2002.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Glomus Tumors: Recognition and Diagnosis

Abstract: Because this is a very uncommon illness, the present series allowed the demonstration of the wide variety of epidemiologic and clinical aspects described in the literature, with the presentation of elements that may improve its recognition and diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Immunostaining with antismooth muscle actin, however, highlights the tumor cells and, together with negative cytokeratin staining, rules out any suspicion of cystic sialoadenoma. In contrast to solitary glomus tumors, which tend to occur in adulthood, multiple glomus tumors are thought to appear more commonly in childhood or adolescence (8), with rare onset after the age of 30 (9, 10). Review of the previously reported cases of multiple glomus tumors revealed a slight male predominance (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostaining with antismooth muscle actin, however, highlights the tumor cells and, together with negative cytokeratin staining, rules out any suspicion of cystic sialoadenoma. In contrast to solitary glomus tumors, which tend to occur in adulthood, multiple glomus tumors are thought to appear more commonly in childhood or adolescence (8), with rare onset after the age of 30 (9, 10). Review of the previously reported cases of multiple glomus tumors revealed a slight male predominance (8).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to solitary glomus tumors, which tend to occur in adulthood, multiple glomus tumors are thought to appear more commonly in childhood or adolescence (8), with rare onset after the age of 30 (9, 10). Review of the previously reported cases of multiple glomus tumors revealed a slight male predominance (8). Sixty percent of multiple glomus cases had a positive family history, supporting the belief that this abnormality is inherited in an autosomal dominant fashion with incomplete penetrance and variable expressivity.…”
Section: Discussionmentioning
confidence: 99%
“…The term glomus tumor is somewhat confusing though, since it may easily be mixed up with a benign tumor of the subcutaneous skin, the so called glomangioma [2], [14], [15]. The term chemodectoma has first been used by Mulligan in 1950 [16].…”
Section: Introductionmentioning
confidence: 99%